Removal of lead (II) ions from aqueous solution using desiccated coconut waste as low-cost adsorbent - Rahim, A.R.A. (2019)
Waste from coconut milk processing industry namely desiccated coconut waste (DCW) was used to remove Pb (II) due to Pb (II) hazardous effect in the environment. The main objective of this study is to study and develop the adsorption capability of the DCW adsorbent. The chemical and physical properties of the DCW adsorbent were depicted by the FT-IR spectra and the elemental CHNS analysis. The maximum Pb (II) adsorption capacity (Q) toward DCW adsorbent was 50.33 mg/g at pH solution of 6 with the rate of 0.004 mg/min. In addition, the Pb (II) equilibrium data were best fitted to the Langmuir isotherm model, whereas the kinetic data obeyed the pseudo-second-order kinetic model. In the regeneration study, DCW adsorbent has remained stable up to two adsorption cycles. Thus, these satisfactory results revealed that the use of DCW as an alternative low-cost adsorbent for the removal Pb (II) from aqueous solution is feasible. Copyright Â© 2019, AIDIC Servizi S.r.l.